Using JSON-LD and Hydra for Cloud-Based Tool Interoperability: A prototype Based on a Vocabulary and Communication Process Handler for Mind Map Tools - Hernandez, R.; Guetl, Christian; Amado-Salvatierra, H. (Springer International Publishing, 2014)
Learning tools interoperability is a well-identified challenge tackled by different approaches such as the IMS Global LTlv2 definition. This paper presents a study to achieve interoperability in a cloud-based educational environment for external tools loosely coupled to form a virtual learning environment. This research builds on the W3C community group project Hydra to achieve interoperability for Web-service-based learning tools. A proof of concept is presented for one selected mind map tool supporting learning activities. The approach uses Web API descriptions based on a generic vocabulary built on Hydra and JSON-LD. A proposed communication process handler is presented in order to enable the interoperability. Initial results demonstrate that interoperability is highly efficient by means of a higher level of abstraction, while it simplifies the definition and coupling process of cloud-based tools.